Refractory Errors; Myopia V/S Hypermetropia And Eye Correction Techniques Used Among Adult Population Visiting A Tertiary Care Health Facility - Ayla Amin, Amaima Gulzar, Iqtaza Arif, Arooj Zulfiqar, Iqra Javed, Muhammad Rizwan Khan, Ayla Amin, Amaima Gulzar, Iqtaza Arif, Arooj Zulfiqar, Iqra Javed, Muhammad Rizwan Khan (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Uncorrected refractory errors are one of the major causes of avoidable disabilities all over the world. Eye correction is a commonly used treatment technique for most of the refractive errors. We attempted to assess the frequencies of myopia and hypermetropia in adult population and also the magnitude of eye correction techniques used for these conditions. Methods: This descriptive cross-sectional study was conducted in the outpatient departments of the allied hospitals of Rawalpindi Medical University. Adult attendants of the patients coming in OPD were selected through stratified random sampling. Participants with any ophthalmological condition other than myopia or hypermetropia, or any other known medical, surgical or gynaecological condition were excluded from the study. Auto-refraction was performed by optometrist followed by an assessment of visual acuity using Snellen’s chart for far vision. Information was also collected regarding eye correction techniques being used by already diagnosed patients. Results: Out of 207 study participants refractive errors were diagnosed in 87 (42%) participants whereas 120 (58%) participants had emmetropia. Amongst 87 patients with refractive errors, 77 (88.5%) participants had myopia, 7 (8%) were hypermetropic and 3 (3.4%) had both myopia and hypermetropia. 45 (51.7%) participants were already known cases of refractory errors previously and only 51.1% of those were using spectacles for correction whereas none of them had ever used contact lenses or corrective laser or surgical intervention for any correction. Conclusion: Myopia was the commonest refractory error diagnosed whereas hypermetropia and both hypermetropia and myopia concurrently were exceedingly rare. None of the already known cases of refractive errors had ever used contact lenses or laser or surgical intervention for correction where only half of them were using spectacles